LBX, Little Battlers experience. Volume 6, World battle - Fujii, Hideaki, 1977-; Sitterson, Aubrey (Fujii, Hideaki, 1977- Danball senki., 2015)
"Van and Hiro arrive at Eden, where they are must fight against Alfred Gordon and his formidable LBX, Zeus. Trouble arises when Eden's two computers, Adam and Eve awaken Misère--an android that Gordon had originally planned on using to attain world dominance. It's time for Van and Hiro's final battle!"--page [4] of cover.